2006
DOI: 10.1016/j.ejvs.2006.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The PADHOC Device is a Better Guide to the Actual Incapacity Suffered by Claudicants than the Gold Standard Constant Load Treadmill Test

Abstract: The DPWT is more representative of the functional incapacity experienced by patients with intermittent claudication. We believe that the PADHOC is a suitable alternative to the CLTT in the assessment of this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A specific ultrasound device (PADHOC; Peripheral Arterial Disease Holter Control) was developed to monitor the distance walked by measuring the distance between the ankles. 28,33 With this device, MWD was correlated with MWD TT (rϭ0.60, PϽ0.01) in PAD patients, 28 although the median PADHOC MWD until the first observed stop during flat walking at usual speed was on average Ϸ2 times higher than the median MWD TT (2.5 km/h on a 10% grade) as also observed for supervised indoor tests. 32 The PADHOC system is an interesting tool for vascular specialists but is not readily available to most physicians.…”
Section: Le Faucheur Et Al Outdoor Walking Capacity Assessed By Gps Imentioning
confidence: 85%
See 1 more Smart Citation
“…A specific ultrasound device (PADHOC; Peripheral Arterial Disease Holter Control) was developed to monitor the distance walked by measuring the distance between the ankles. 28,33 With this device, MWD was correlated with MWD TT (rϭ0.60, PϽ0.01) in PAD patients, 28 although the median PADHOC MWD until the first observed stop during flat walking at usual speed was on average Ϸ2 times higher than the median MWD TT (2.5 km/h on a 10% grade) as also observed for supervised indoor tests. 32 The PADHOC system is an interesting tool for vascular specialists but is not readily available to most physicians.…”
Section: Le Faucheur Et Al Outdoor Walking Capacity Assessed By Gps Imentioning
confidence: 85%
“…The fact that MWD GPS was higher than MWD TT is consistent with previous studies that showed that MWD determined from unconstrained walking was vastly greater than MWD TT . 3,28,29,31,32 This does not suggest that reliance on MWD GPS estimation is flawed but rather that treadmill testing does not satisfactorily reflect unconstrained outdoor walking. GPS recording of unconstrained outdoor walking appears to be an attractive approach for future studies in PAD patients or patients who have nonvascular walking limitations (eg, cardiac insufficiency or bronchitis).…”
Section: Le Faucheur Et Al Outdoor Walking Capacity Assessed By Gps Imentioning
confidence: 98%